DETERMINING PRE-SERVICE SCIENCE TEACHERS' UNDERSTANDING ABOUT STEM EDUCATION - Kececi, Gonca (Sci Methodical Ctr-Sci Educologica, 2023)
STEM education is included in education programs by many countries on a global scale. Pre-service teachers are also expected to apply STEM education in their future classrooms. The aim of the research was to determine how pre-service science teachers perceived STEM education, whether they adopted it or not, whether they thought of themselves as sufficient, and the environment and situations that affected their STEM experience. The understanding of the pre-service science teachers was tried to be determined before the theoretical STEM education, after the theoretical education and after the STEM application. The study group of the research consisted of a total of 66 pre-service teachers. Content analysis results of the interviews were carried out in three stages. It was found that there was no single STEM definition that pre-service science teachers agreed on. The training provided increased the STEM competency levels of pre-service science teachers. However, the majority of pre-service science teachers defined themselves as having intermediate competence in STEM education. Pre-service teachers adopt STEM education and believe that it will contribute to students. Pre-service science teachers had the most difficulty in disciplinar y integration during the STEM theory and practice education. The most preferred model after both theoretical knowledge and application was the problem-based STEM model.
Keywords: content analysis; pre-service science teachers; STEM education; STEM understanding